Hyaluronan self-agglomerating nanoparticles for non-small cell lung cancer targeting - Kim, Joo Eun; Park, Young Joon (Cancer Nanotechnology, 2022)
Background: Owing to the limited amount of research, there are no nanoparticle-based anticancer agents that use hydrophilic drugs. Therefore, we developed irinotecan-loaded self-agglomerating hyaluronan nanoparticles (ISHNs). While irinotecan has high hydrophilicity, the resulting nanoparticle should possess high anticancer drug-loading capacity and allow selective targeting of the cluster of differentiation 44 (CD44) protein, which is overexpressed on the surface of tumor cells. Results: The ISHNs were successfully made with hyaluronan (HA) as a targeting moiety, FeCl3 as a binder, and D-glutamic acid (GA) as a stabilizer. The ISHNs self-agglomerated via chelating bonding and were lyophilized using a freeze dryer. The particle diameter and zeta potential of the ISHNs were 93.8 ± 4.48 nm and − 36.3 ± 0.28 mV, respectively; a relatively narrow size distribution was observed. The drug fixation yield and drug-loading concentration were 58.3% and 1.75 mg/mL, respectively. Affinity studies revealed a tenfold stronger targeting to H23 (CD44+) non-small-cell lung cancer (NSCLC) cells, than of A549 (CD44−) cells. Conclusion: We developed irinotecan-loaded ISHNs, which comprised irinotecan hydrochloride as a water-soluble anticancer agent, HA as a targeting moiety, FeCl3 as a binder for self-agglomeration, and GA as a stabilizer; HA is a binding material for CD44 in NSCLC cells. Owing to their ease of manufacture, excellent stability, non-cell toxicity and CD44-targeting ability, ISHNs are potential nanocarriers for passive and active tumor targeting.
Keywords: Hyaluronan; Irinotecan; Nanoparticle; NSCLC; Stability; Targeting